A CONSULTA POPULAR COMO ESTRATÉGIA DE PLANEJAMENTO PARA O DESENVOLVIMENTO SOCIOECONÔMICO REGIONAL - WESENDONCK, CLAUDIA C.; SIEDENBERG, DIETER R.; MALETZ, EDISON A.; SOUZA, JOSÉ D. D.; PETERSEN, LETÍCIA L.; RI, MARLENE K. D.; SILVA, PALOMA E. Z. D.; DALLEPIANE, SABRINA; ALLEBRANDT, SERGIO L.; DUTRA, VIVIANE B. (Salão do Conhecimento, 2013)
Resumo